MANDAR MARTIAL ARTS TRADITIONS:AS A CHARACTER TO DEVELOP TOURISM ON TIDUNG ISLAND KEPULAUAN SERIBU DKI JAKARTA - Siti Gomo Attas; Gres Grasia Azmin; Marwiah Marwiah; Sarmadan Sarmadan (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2023)
The Silat Mandar tradition can shape the character of the people of Tidung Island in order to develop tourism on Tidung Island. Silat Mandar is able to give color to people's lives in the DKI Jakarta area, especially Tidung Island in Kepualauan Seribu. Starting from the mythology of Bugis Mandar as an accomplished sailor, making the Bugis Mandar people a society that is undaunted to sail the ocean, such as the Bugis proverb